Spectrally Resolved Characterization of Thermally Induced Underwater Turbulence Using a Broadband White-Light Interrogator - Omar Alkhazragi; Xiaobin Sun; Viktor Zuba; El-Mehdi Amhoud; Hassan Oubei; Tien Khee Ng; Burton Jones; Mohamed-Slim Alouini; Boon S. Ooi (IEEE Photonics Journal)
To allow for reliable wireless optical links in realistic underwater environments, we study the dependence of turbulence-induced fading on the wavelength using a laser-based white-light interrogator in emulated realistic conditions. We experimentally show that the scintillation index decreases significantly with the increase of wavelength. The results are verified for longer distances using a Monte Carlo simulation. We numerically and experimentally demonstrate that the use of longer wavelengths lowers the bit error ratio by as much as three orders of magnitude. We conclude that using green light is more reliable in turbulent channels than blue. The correlation between different wavelengths under turbulence is studied, which was made possible by the use of the laser-based white-light interrogator.